On the Impact of Linear Siloxanated Side Chains on the Molecular Self‐Assembling and Charge Transport Properties of Conjugated Polymers. (3rd November 2020) - Kamatham, Narayanaswamy; Ibraikulov, Olzhas A.; Durand, Pablo; Wang, Jing; Boyron, Olivier; Heinrich, Benoît; Heiser, Thomas; Lévêque, Patrick; Leclerc, Nicolas; Méry, Stéphane
Abstract: Herein reported is the impact of the functionalization of four different semiconducting polymer structures by a linear siloxane‐terminated side‐chains. The latter is tetrasiloxane (Si4 ) or trisiloxane (Si3 ) chains, substituted at their extremity to a pentylene linker. The polymer structure is based on 5, 6‐difluorobenzothiadiazole comonomer (PF2), a diketopyrrolopyrrole unit (PDPP‐TT), a naphtalediimide unit (PNDI‐T2 ), and a poly[bis(thiophen‐2‐yl)thieno[3, 2, b]thiophene (PBTTT). The properties of these siloxane‐functionalized polymers are scrutinized and compared with the ones of their alkyl‐substituted polymer analogues. The impact of the alkyl‐to‐siloxane chain substitution clearly depends on the molecular section of the side chains. When a branched 2‐octyldodecyl chain (C20 ) is replaced by a Si4 chain of same molecular section, the greatest impact is the strong increase of the π‐stacking overlap of the polymer backbones. This effect leads to a significative enhancement of the charge mobility values of the polymers. As in‐plane and out‐of‐plane mobility are increased simultaneously, this π‐overlap enhancement effect happens to be preponderant over the polymer orientation variations. When a linear tetradecyl chain (C14 ) is replaced by a linear Si3 chain of twice larger molecular section, the polymer structure is profoundly affected. While PBTTT‐C14 is crystalline and purely edge‐on, PBTTT‐Si3 is mesomorphic and shows a mixed face‐on/edge‐on orientation. Abstract : The origin of the enhanced charge transport properties in siloxane‐functionalized p‐conjugated polymers is demonstrated. By scrutinizing the fine structural organization induced by linear siloxane and ramified alkyl side‐chains of same molecular section, it is observed that the unique fluidity and segregation propensity of siloxane chains drive the siloxane‐functionalized polymers to a considerable increase of the p‐stacking backbone overlap.